The myths of standardized tests : why they don't tell you what you think they do - Harris, Phillip, 1939-; Smith, Bruce M., 1949-; Harris, Joan, 1938- (Lanham, Md. : Rowman & Littlefield Pub., 2011)
Debunks myths and assumptions about standardized tests, proposes alternative methods for evaluating the success of schools, and offers suggestions for helping to reduce the burden of tests on students.
Includes bibliographical references (p. 173-186) and index.
Keywords: Universities and colleges -- United States -- Admission; Education, Higher -- Standards -- United States; College applications -- United States